Oxidative stress, metabolism of ethanol and alcohol-related diseases - Zima, T; Fialová, L; Mestek, O; Janebová, M; Crkovská, J; Malbohan, I; Stípek, S; Mikulíková, L; Popov, P (Journal of biomedical science, 2001)
Alcohol-induced oxidative stress is linked to the metabolism of ethanol. Three metabolic pathways of ethanol have been described in the human body so far. They involve the following enzymes: alcohol dehydrogenase, microsomal ethanol oxidation system (MEOS) and catalase. Each of these pathways could produce free radicals which affect the antioxidant system. Ethanol per se, hyperlactacidemia and elevated NADH increase xanthine oxidase activity, which results in the production of superoxide. Lipid peroxidation and superoxide production correlate with the amount of cytochrome P450 2E1. MEOS aggravates the oxidative stress directly as well as indirectly by impairing the defense systems. Hydroxyethyl radicals are probably involved in the alkylation of hepatic proteins. Nitric oxide (NO) is one of the key factors contributing to the vessel wall homeostasis, an important mediator of the vascular tone and neuronal transduction, and has cytotoxic effects. Stable metabolites--nitrites and nitrates--were increased in alcoholics (34.3 +/- 2.6 vs. 22.7 +/- 1.2 micromol/l, p < 0.001). High NO concentration could be discussed for its excitotoxicity and may be linked to cytotoxicity in neurons, glia and myelin. Formation of NO has been linked to an increased preference for and tolerance to alcohol in recent studies. Increased NO biosynthesis also via inducible NO synthase (NOS, chronic stimulation) may contribute to platelet and endothelial dysfunctions. Comparison of chronically ethanol-fed rats and controls demonstrates that exposure to ethanol causes a decrease in NADPH diaphorase activity (neuronal NOS) in neurons and fibers of the cerebellar cortex and superior colliculus (stratum griseum superficiale and intermedium) in rats. These changes in the highly organized structure contribute to the motor disturbances, which are associated with alcohol abuse. Antiphospholipid antibodies (APA) in alcoholic patients seem to reflect membrane lesions, impairment of immunological reactivity, liver disease progression, and they correlate significantly with the disease severity. The low-density lipoprotein (LDL) oxidation is supposed to be one of the most important pathogenic mechanisms of atherogenesis, and antibodies against oxidized LDL (oxLDL) are some kind of epiphenomenon of this process. We studied IgG oxLDL and four APA (anticardiolipin, antiphosphatidylserine, antiphosphatidylethanolamine and antiphosphatidylcholine antibodies). The IgG oxLDL (406.4 +/- 52.5 vs. 499.9 +/- 52.5 mU/ml) was not affected in alcoholic patients, but oxLDL was higher (71.6 +/- 4.1 vs. 44.2 +/- 2.7 micromol/l, p < 0.001). The prevalence of studied APA in alcoholics with mildly affected liver function was higher than in controls, but not significantly. On the contrary, changes of autoantibodies to IgG oxLDL revealed a wide range of IgG oxLDL titers in a healthy population. These parameters do not appear to be very promising for the evaluation of the risk of atherosclerosis. Free radicals increase the oxidative modification of LDL. This is one of the most important mechanisms, which increases cardiovascular risk in chronic alcoholic patients. Important enzymatic antioxidant systems - superoxide dismutase and glutathione peroxidase - are decreased in alcoholics. We did not find any changes of serum retinol and tocopherol concentrations in alcoholics, and blood and plasma selenium and copper levels were unchanged as well. Only the zinc concentration was decreased in plasma. It could be related to the impairment of the immune system in alcoholics. Measurement of these parameters in blood compartments does not seem to indicate a possible organ, e.g. liver deficiency.
Keywords: Liver; dospělí; Lipoproteins, LDL; Antioxidants; jaterní testy; glutamylaminopeptidasa; oxidační stres; játra; stopové prvky; Glutamyl Aminopeptidase; ethanol; Adult; aminopeptidasy; Free Radicals; Oxidative Stress; Trace Elements; lidé; fosfolipidy; alkoholismus; studie případů a kontrol; Ethanol; Humans; Alcoholism; Case-Control Studies; Autoantibodies; Phospholipids; Alcohol-Related Disorders; antioxidancia; Nitric Oxide; Aminopeptidases; oxid dusnatý; lidé středního věku; gamma-Glutamyltransferase; Liver Function Tests; poruchy způsobené alkoholem; Middle Aged; lipoproteiny LDL; gama-glutamyltransferasa; volné radikály; autoprotilátky